Predictive abilities of cardiovascular biomarkers to rapid decline of renal function in Chinese community-dwelling population: a 5-year prospective analysis - Fu, Shihui (BMC Nephrol, 2017)
BACKGROUND: Predictive abilities of cardiovascular biomarkers to renal function decline are more significant in Chinese community-dwelling population without glomerular filtration rate (GFR) below 60 ml/min/1.73m(2), and long-term prospective study is an optimal choice to explore this problem. Aim of this analysis was to observe this problem during the follow-up of 5 years. METHODS: In a large medical check-up program in Beijing, there were 948 participants with renal function evaluated at baseline and follow-up of 5 years. Physical examinations were performed by well-trained physicians. Blood samples were analyzed by qualified technicians in central laboratory. RESULTS: Median rate of renal function decline was 1.46 (0.42–2.91) mL/min/1.73m(2)/year. Rapid decline of renal function had a prevalence of 23.5% (223 participants). Multivariate linear and Logistic regression analyses confirmed that age, sex, baseline GFR, homocysteine and N-terminal pro B-type natriuretic peptide (NT-proBNP) had independently predictive abilities to renal function decline rate and rapid decline of renal function (p < 0.05 for all). High-sensitivity cardiac troponin T (hs-cTnT), carotid femoral pulse wave velocity and central augmentation index had no statistically independent association with renal function decline rate and rapid decline of renal function (p > 0.05 for all). CONCLUSIONS: Homocysteine and NT-proBNP rather than hs-cTnT had independently predictive abilities to rapid decline of renal function in Chinese community-dwelling population without GFR below 60 ml/min/1.73m(2). Baseline GFR was an independent factor predicting the rapid decline of renal function. Arterial stiffness and compliance had no independent effect on rapid decline of renal function. This analysis has a significant implication for public health, and changing the homocysteine and NT-proBNP levels might slow the rapid decline of renal function.